A new species of Hemicaecilius Enderlein based on a male from Cuzco, Peru (Psocodea: ‘Psocoptera’: Lachesillidae) - García Aldrete, Alfonso N.; Mockford, Edward L. (Instituto de Ecología, A.C., 2011)
A new species of Hemicaecilius Enderlein is here described and illustrated. It is based on a male collected near Machu Picchu, Peru, that constitutes the third specimen and the first male knownin the genus. Its morphology confirms the closeness with Nadleria Badonnel & García Aldrete, that had been established on basis of female characters. The holotype is deposited in the National Insect Collection, Instituto de Biología, Universidad Nacional Autónoma de México, Mexico City (coden CNIN).